1996
DOI: 10.1021/bi9510789
|View full text |Cite
|
Sign up to set email alerts
|

4-Oxalocrotonate Tautomerase:  pH Dependence of Catalysis and pKa Values of Active Site Residues

Abstract: The pH-rate profiles for the kinetic parameters of 4-oxalocrotonate tautomerase (4-OT) have been measured using 2-hydroxy-2,4-hexadiendioate (2a) and 2-hydroxy-2,4-pentadienoate (2b) as substrates. The pH dependences of log (kcat/Km) and of log kcat for the slow, nonsticky substrate 2b, which lacks a 6-carboxyl group, were bell-shaped with limiting slopes of unity on both sides of the pH optimum. For 2b, pKa values of 6.2 +/- 0.3 and 9.0 +/- 0.3 for the free enzyme (pKE) and 7.7 +/- 0.3 and 8.5 +/- 0.3 for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

17
227
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 123 publications
(244 citation statements)
references
References 35 publications
17
227
0
Order By: Relevance
“…A pK, value of 6.4 for Pro-I was determined by "N-NMR titration and this pK, is 3 units lower than the model compound proline amide (Stivers et al, 1996a), most likely the result of an active site of low dielectric constant. The pH dependenceof the reaction rate (Stivers et al, 1996a) also suggested a requirement for an enzymic general acid (AH, Fig. 1) with a pK, of 9.0, to stabilize the developing negative charge on the carbonyl oxygen (Xue et al, 1990;Gerlt & Gassman, 1993).…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…A pK, value of 6.4 for Pro-I was determined by "N-NMR titration and this pK, is 3 units lower than the model compound proline amide (Stivers et al, 1996a), most likely the result of an active site of low dielectric constant. The pH dependenceof the reaction rate (Stivers et al, 1996a) also suggested a requirement for an enzymic general acid (AH, Fig. 1) with a pK, of 9.0, to stabilize the developing negative charge on the carbonyl oxygen (Xue et al, 1990;Gerlt & Gassman, 1993).…”
mentioning
confidence: 94%
“…1) is the catalytic base (Stivers et al, 1996a(Stivers et al, , 1996b. A pK, value of 6.4 for Pro-I was determined by "N-NMR titration and this pK, is 3 units lower than the model compound proline amide (Stivers et al, 1996a), most likely the result of an active site of low dielectric constant. The pH dependenceof the reaction rate (Stivers et al, 1996a) also suggested a requirement for an enzymic general acid (AH, Fig.…”
mentioning
confidence: 99%
See 3 more Smart Citations